An integrated map of cattle candidate genes for mastitis - Ogorevc, Jernej (Acta agriculturae slovenica. Suplement, 2008)
To facilitate the development of new genetic markers for mastitis resistance or susceptibility we used genome-wide comparative approach to review all known mastitis-associated loci. We assembled into a map 233 loci that were identified by six different studz approaches (QTLs, association studies, expression experiments, AFLP-, miRNA- and epigenetic- studies). To integrate data from different sources and to identify overlapping regions we presented the results in the form of genetic map. The collected data represent genetic background for mastitis-related traits in cattle. Thirty most promising candidate genes (associated with mastitis in different study approaches or at least in two independent studies, or/and overlapping with QTL regions) were selected from database and in silico searched for genetic variability and putative miRNA target sites in 3'UTR. Thirty-one SNPs in the putative promoter/5' UTR (up to 2 kb upstream) of eight candidate genes were found. Bioinformatic analysis revealed that some promoter SNPs might potentially cause gain/loss of the putative transcription factors. Promoter SNPs were alsopresent in CG dinucleotides and therefore possibly involved in gain/loss of CpG sites. In ten mastitis candidate genes we found 56 SNPs in exons of which 21 were non-synonymous substitutions. Additionally, 23 SNPs in intronic regions and 21 SNPs in 3'UTR were found. MiRNA target analysis revealed 89 putative target sites in 18 candidate genes; however, current SNPs were not identified in the miRNA target binding sites or miRNAs expressed in mammary gland. For SNPs with a putative regulatory role found in candidate genes, functional analyses and association studies are needed to facilitate identification of mastitis resistance or susceptibility alleles possibly involved in mastitis regulatory pathways.
Keywords: candidate genes; cattle; govedo; kandidatni geni; kvantitativni lokusi; mastitis; molecular genetics; molekularna genetika; QTL; quantitative trait loci